DEVELOPMENT STAGES OF PHYSICAL EDUCATION, SPORTS AND NATIONAL GAMES IN UZBEKISTAN - Kamola Muradova (Proximus Journal Publishing, 2024)
During this period of independence in Uzbekistan, major events were held, focusing on the restoration and development of sports and National Games. Great attention has begun to develop many mass sports in these years. It was aimed at turning people into a way of life Physical education and sports. In its place, strengthening the reserve of professional sports through the development of mass sports, it was aimed at growing sports indicators
Keywords: Mass Sports; national struggle; folk National Games; physical education